THE ROLE OF WOMEN IN THE CULTURAL SPHERIES OF THE SOVIET ERA - Uraimjonova Malika Qahramon qizi (American Journals, 2023)
The article summarizes the cultural and practical life of the Soviet Union, which analyzes the role of women and their direct participation in cultural reforms. It can be said that during the Soviet era, women served as a source of childcare and the development of local culture, despite the fact that there were many barriers and unnecessary restrictions not only in social but also in cultural and educational fields.
Keywords: Women of the Former Union, culture and education, cultural reforms, feminism.